The Construction and the Negotiation of Ethnographic Voices Notes From an Italian Post-Industrial Area - Rimoldi, Luca (Richtmann Publishing, 2012)
Oral sources vary according to their specific use in a particular social arena. In this respect, the ethnographic encounter is acontext where significant discourses and narratives about the past are produced, both at the institutional and individual level. Even if lessimmediately evident, also written sources are the products of specific historical, political, and cultural agendas. This paper is intended asa methodological reflection on the socio-political construction of oral and written sources in the context of extensive fieldwork, carried outbetween 2008 and 2010, in a post-industrial area of the city of Milan, Italy known as Bicocca. Today, the University of Milano Bicocca, theTheatre Arcimboldi, CNR, and Siemens Italia, among others, occupy the site. However, until the 1980s, the same area hosted the PirelliIndustries, one of the major Italian plants for the production of plastics, tires, and cables. Even if the site has subsequently beentransformed into a â€œtechnological integrated areaâ€, it is still permeated with both material and immaterial historical traces of its industrialpast. I consider here the historical archive of the Pirelli Industries and my conversations with former unionists and workers of the Pirelli; Ifocus on the accounts of the years 1968-1969, also known as the â€œSecond Red Bienniumâ€ or the â€œAutunno Caldoâ€, an exceptional phaseof two years of intense demonstrations and strikes. I explore both archival sources and personal accounts, in short: the plurality of voicesthat are part of the siteâ€™s memory, past and present. My analysis will stress a specific methodological issue that is the need of amultidisciplinary approach in the context of my fieldwork research, given the malleability of the concept of memory itself and consideringthe fruitful collaboration between anthropology, oral history and the sociology of memory.